Oil and gas potential of the deep-lying Jurassic and pre Jurassic deposits of the North of Western Siberia in unconventional traps - V. L. Shuster; S. A. Punanova (Georesursy, 2024)
In-depth additional studies were carried out to assess oil and gas potential of deep-lying Jurassic and pre-Jurassic deposits of the northern territories of Western Siberia. As in previous work, the geological and mathematical program “Vybor” was used. Based on the first constructed series of model maps with probabilistic values of informative geochemical and geological parameters, the most promising both local and regional objects were selected.Increasing complexity of the traps structure with depth was noted. As a rule, from the Cretaceous deposits to the Jurassic and Paleozoic, the type of trap from the predominant anticline (in the Cretaceous) changes to a much more complex combined one, which requires special approaches (and new technologies) to identify and explore such objects. Studies based mainly on seismic data indicate rather high oil and gas content of both the Paleozoic and Triassic deposits, which have a platform occurence and large thicknesses, as well as crystalline basement formations. In this regard, unconventional combined traps of deep-lying deposits of the North of Western Siberia are of significant interest in terms of incremental oil and gas resources and reserves.